Faculty awareness and use of adult learning principles - Patricia A. Lawler; Arlene D. DeCosmo; Stephen C. Wilhite (Adult Education Research Conference, 1996)
This research explored the awareness and use of adult learning strategies by faculty in a mid-size comprehensive university. Through initial and follow-up surveys and interviews, participants in a faculty development initiative reported an awareness of, but little use of these strategies prior to attending the workshops. Results suggest that faculty development programs should be focused on implementation issues. Researchers found a rich pool of data to be used in planning subsequent workshops.